Planning for Crime Prevention - Kitchen, Ted (RTPI Library Series, 2002)
Crime and the fear of crime are issues high in public concern and on political agendas in most developed countries. This book takes these issues and relates them to the contribution that urban planners and participative planning processes can make in response to these problems. Its focus is thus on the extent to which crime opportunities can be prevented or reduced through the design, planning and management of the built environment. The perspective of the book is transatlantic and comparative, not only because ideas and inspiration in this and many other fields increasingly move between countries but also because there is a great deal of relevant theoretical material and practice in both the USA and the UK which has not previously been pulled together in this systemic manner.